calculus
posted by Dan .
find the following derivatives:
f(x) = (2x+5)/(x^23)
f'(x)= (2)*(x^2 3)(2x+5)*2x/(x^23)^2
is that correct???
f(x)= (lnx)(cos x)
f'(x)= 1/x*sinx
or do i have to use the product rule??
thank you.

the first one is correct, with the second you have to use the product rule
Respond to this Question
Similar Questions

CALC
find the following derivatives: f(x) = (2x+5)/(x^23) f'(x)= (2)*(x^2 3)(2x+5)*2x/(x^23)^2 is that correct? 
calculus
Could someone check my reasoning? thanx Find the derivative of the function. sin(sin[sinx]) I need to use the chain rule to solve. So I take the derivative sin(sin[sinx) first. Then multiply that by the inside which is the derivative 
Calculus
Find the derivative of y with respect to x. y= [(x^5)/5]lnx[(x^5)/25] How would I go about doing this? 
Calculus (Derivatives)
Using the product rule, find the derivative of the following function: (x^1/2 cscx sinx). 
College Calc
Problem: y=sqrtx ^1/x. Find DY/DX. ln(f(x))=lnx^1/2x or lnx to the 1/2x 1/2x lnx product rule (1/4x^2)(lnx)+(1/x)(1/2x) is the product rule correct? 
Calculus
Find the derivatives, dy/dx for the following functions. a. x^2y^4 = lnx + 3y b. y = ln(2x^2 + 1) c. y = ln(ãx) d. y = lnx/x e. y = x^2 lnx f. y ß log_2(3x) 
Calculus
Find the outside and inside functions of the following to find their derivatives: 1) sqrt(2x+9) 2) cos(cos(x)) 3) tan(x) I already know how to find their derivatives I'm just not exactly sure what parts of the chain rule equation would … 
Derivatives
Find the derivatives of: 1. H(x)= sin2xcos2x The answer given is 2cos4x. My question is, how in the world did they get that!? 
Calculus
Find the derivatives of the following 18. y=〖cos〗^4 x^4 ANSWER: tanx2 19. y= sinx/(1+ 〖cos〗^2 x) ANSWER: 3sinx 20. y=sinx(sinx+cosx) ANSWER: sinx Can you check my answers? 
Calculus
Just got through with derivatives, power rule, and chain rule. I am supposed to find the first and second derivatives of the function. y = 4x/√x+1 and y = cos^2(x) y' = [(x+1)^(1/2)(4)][(4x)(1/2(x+1)^(1/2))(1)] y' = [4(x+1)^(1/2)4x]/[2(x+1)^(1/2)(x+1)] …